Within-host evolution of a Klebsiella pneumoniae clone: selected mutations associated with the alteration of outer membrane protein expression conferred multidrug resistance. (25th October 2020) - Aihara, Masamune; Nishida, Ruriko; Akimoto, Masaru; Gotoh, Yasuhiro; Kiyosuke, Makiko; Uchiumi, Takeshi; Nishioka, Mitsuaki; Matsushima, Yuichi; Hayashi, Tetsuya; Kang, Dongchon
Abstract: Background: A patient repeatedly developed bacteraemia despite the continuous use of antibiotics. We obtained two Klebsiella pneumoniae isolates from the patient's blood on Days 72 and 105 after hospitalization. Each of the two isolates belonged to ST45, but while the first isolate was susceptible to most antibiotics, the second one was resistant to multiple drugs including carbapenems. Objectives: To identify the genetic differences between the two isolates and uncover alterations formed by the within-host bacterial evolution leading to the antimicrobial resistance. Methods: Whole-genome comparison of the two isolates was carried out to identify their genetic differences. We then profiled their outer membrane proteins related to membrane permeability to drugs. To characterize a ramR gene mutation found in the MDR isolate, its WT and mutant genes were cloned and expressed in the MDR isolate. Results: The two isolates showed only three genomic differences, located in mdoH, ramR and upstream of ompK36 . In the MDR isolate, a single nucleotide substitution in the ompK36 upstream region attenuated OmpK36 expression. A single amino acid residue insertion in RamR in the MDR isolate impaired its function, leading to the down-regulation of OmpK35 and the subsequent up-regulation of the AcrAB-TolC transporter, which may contribute to the MDR. Conclusions: We identified very limited genomic changes in the second K. pneumoniae clone during within-host evolution, but two of the three identified mutations conferred the MDR phenotype on the clone by modulating drug permeability.